2004
DOI: 10.1177/0148607104028006399
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Glucagon‐Like Peptide‐2 (GLP‐2), Growth Hormone (GH), and Keratinocyte Growth Factor (KGF) on Markers of Gut Adaptation After Massive Small Bowel Resection in Rats

Abstract: GLP-2 exerts superior trophic effects on jejunal growth and also improves mucosal glutathione redox status throughout the bowel after massive SBR in rats. Both GH and KGF increase colonic mucosal growth in this model. KGF alone potently increases gut mucosal goblet cell number and expression of the cytoprotective trefoil peptide TFF3. The differential effects of GLP-2, GH and KGF administration in this model of short bowel syndrome suggest that individual therapy with these growth factors may not be an adequat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 65 publications
2
45
0
Order By: Relevance
“…Quantification of lipid peroxidation and ␣-tocopherol along the crypt-villus axis are consistent with increased oxidative stress in crypt stem cells and villus tip cells (29). Furthermore, following partial small bowel resection, the glutathione redox potential is shifted to a more oxidized state in the ileal remnant (62). Thus the observed prosurvival effects of RA postresection may be mediated by reducing oxidant stress in actively proliferating crypt cells.…”
Section: Discussionmentioning
confidence: 63%
“…Quantification of lipid peroxidation and ␣-tocopherol along the crypt-villus axis are consistent with increased oxidative stress in crypt stem cells and villus tip cells (29). Furthermore, following partial small bowel resection, the glutathione redox potential is shifted to a more oxidized state in the ileal remnant (62). Thus the observed prosurvival effects of RA postresection may be mediated by reducing oxidant stress in actively proliferating crypt cells.…”
Section: Discussionmentioning
confidence: 63%
“…5). It was something of a surprise that neither of these factors appeared to be linked to the decreases in apoptosis seen in the bypass animals because they both have been suggested to play a role in the control of mucosal apoptosis [46,47]. Thus, it may be other factors, specific signals, a combination of factors, or variations in the sensitivity to trophic ligands induced by changes in receptor expression, which control apoptosis and the morphological adaptation that is stimulated by nutrient contact [46,48].…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to the more marked effect of IGF-I ablation on both small and large intestinal growth responses to GLP-2. Moreover, unlike IGF-I, KGF treatment produces differential effects to those of GLP-2, affecting mainly colonic growth and the differentiation of goblet cells (2,22,42). Indeed, Ørskov et al (32) found that the GLP-2-induced increase in mucin expression was blocked by KGF antibodies, suggesting that the specific role of KGF may be to promote colonic goblet cell differentiation in response to GLP-2.…”
Section: Multiple Actions Multiple Mediatorsmentioning
confidence: 99%